Release of nitric oxide from glyceryl trinitrate by captopril but not enalaprilat: in vitro and in vivo studies. - Salvemini, D. (Nature Publishing Group, 1993)
1. The hypotensive effects of glyceryl trinitrate (GTN, 0.5 mg kg-1) but not of 3-morpholino-sydnonimine (SIN-1, 0.125 mg kg-1) in anaesthetized rats were attenuated following a seven day (using a q.i.d. dosing schedule) oral treatment with isosorbide-5-mononitrate (IS-5-MN; 5 mg kg-1) indicative of the induction of tolerance to GTN but not to SIN-1. The hypotensive effects of GTN did not decline when the sulphydryl (SH) containing angiotensin converting enzyme inhibitor (ACE-1), captopril (CPT, 5 mg kg-1) or the structurally unrelated SH-containing, N-acetylcysteine (NAC, 10 mg kg-1) but not the non-SH-containing ACE-I, enalaprilat (ENA, 5 mg kg-1) were given together with IS-5-MN for the seven days treatment. 2. The attenuated hypotensive effects of GTN (0.5 mg kg-1) in rats treated with IS-5-MN were also restored when CPT (1 mg kg-1) or NAC (2.5 mg kg-1) but not ENA (1 mg kg-1) was administered intraperitoneally (i.p.) 30 min before GTN. Furthermore, in control rats, CPT or NAC but not ENA given i.p. 30 min before GTN, potentiated its haemodynamic effects. These effects were blocked by methylene blue (10 mg kg-1). At the same doses, CPT or NAC did not affect the hypotensive effects of SIN-1.(ABSTRACT TRUNCATED AT 250 WORDS)